Inside the ‘imperfect mosaic’: Minority ethnic women’s qualitative experiences of race and ethnicity during pregnancy, childbirth, and maternity care in the United Kingdom - Silverio, Sergio A.; Varman, Nila; Barry, Zenab; Khazaezadeh, Nina; Rajasingam, Daghni; Magee, Laura A.; Matthew, Jacqueline (BMC public health, 2023)
Persistent, high rates of maternal mortality amongst ethnic minorities is one of the UK's starkest examples of racial disparity. With greater risks of adverse outcomes during maternity care, ethnic minority women are subjected to embedded, structural and systemic discrimination throughout the healthcare service. Fourteen semi-structured interviews were undertaken with minority ethnic women who had recent experience of UK maternity care. Data pertaining to ethnicity and race were subject to iterative, inductive coding, and constant comparison through Grounded Theory Analysis to test a previously established theory: The 'Imperfect Mosaic'. A related theory emerged, comprising four themes: 'Stopping Short of Agentic Birth'; 'Silenced and Stigmatised through Tick-Box Care'; 'Anticipating Discrimination and the Need for Advocacy'; and 'Navigating Cultural Differences'. The new theory: Inside the 'Imperfect Mosaic', demonstrates experiences of those who received maternity care which directly mirrors experiences of those who provide care, as seen in the previous theory we set-out to test. However, the current theory is based on more traditional and familiar notions of racial discrimination, rather than the nuanced, subtleties of socio-demographic-based micro-aggressions experienced by healthcare professionals. Our findings suggest the need for the following actions: Prioritisation of bodily autonomy and agency in perinatal physical and mental healthcare; expand awareness of social and cultural issues (i.e., moral injury; cultural safety) within the NHS; and undertake diversity training and support, and follow-up of translation of the training into practice, across (maternal) health services.